SCHWARCZ, L. M. (org.) Leituras críticas sobre Evaldo Cabral de Mello. Belo Horizonte: Ed. UFMG; Fundação Perseu Abramo, 2008, 204p. (Em Tempo de Histórias, 2011)
SCHWARCZ, L. M. (org.) Leituras críticas sobre Evaldo Cabral de Mello. Belo Horizonte: Ed. UFMG; Fundação Perseu Abramo, 2008, 204p.